2016
DOI: 10.1038/srep36922
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1/IGF-1R/hsa-let-7c axis regulates the committed differentiation of stem cells from apical papilla

Abstract: Insulin-like growth factor-1 (IGF-1) and its receptor IGF-1R play a paramount role in tooth/bone formation while hsa-let-7c actively participates in the osteogenic differentiation of mesenchymal stem cells. However, the interaction between IGF-1/IGF-1R and hsa-let-7c on the committed differentiation of stem cells from apical papilla (SCAPs) remains unclear. In this study, human SCAPs were isolated and treated with IGF-1 and hsa-let-7c over/low-expression viruses. The odonto/osteogenic differentiation of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 57 publications
(76 reference statements)
1
40
0
Order By: Relevance
“…Then, SCAPs were purified by the procedure of magnetic activated cell sorting (MACS) as previously described. 26 Cells were passaged by 0.25% trypsin at a 1:3 split ratio after the cell density came up to 80-85%. For the follow-up experiments, SCAPs within 3-5 passages were used.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Then, SCAPs were purified by the procedure of magnetic activated cell sorting (MACS) as previously described. 26 Cells were passaged by 0.25% trypsin at a 1:3 split ratio after the cell density came up to 80-85%. For the follow-up experiments, SCAPs within 3-5 passages were used.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…The best parameter of multiplicity of infection (MOI) was 5 as previously reported. 26 SCAPs cultured at 60-70% confluence were transfected with the lentiviruses in 2 mL α-MEM supplemented with 10% FBS and 0.05 mg/mL polybrene (Santa Cruz Biotechnology, Santa Cruz, CA). Ten hours later, the infected cells were incubated in replaced conventional media for further use.…”
Section: Cell Transfectionmentioning
confidence: 99%
“…(D,F) Western blotting analysis of expression of RUNX2, ALP, DSPP, and DMP1 of BMSCs after culturing in different medium at 7 days ( Figure 4D) and 14 days ( Figure 4F). (Ma et al, 2016;Wang et al, 2018;Zhang et al, 2019). To the best of our knowledge, there are no published systemic proteomic analyses that explore the extracellular environment of SCAPs during osteo/odontogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Ma et al [32] showed that the insulin-like growth factor-1 (IGF-1)/IGF-1R/hsa-let-7c axis exerts a key influence on the odontogenic differentiation of IGF-1-treated SCAPs as well as the MAPK signaling pathway. IGF-1 activity is mostly facilitated through IGF-1R and is therefore known as the IGF-1/IGF-1R axis.…”
Section: Anti-odontogenic Differentiation Mirnasmentioning
confidence: 99%
“…Under these conditions, cells have been shown to subsequently express an osteoblast-associated gene profile, including alkaline phosphatase (ALP), collagen type 1 (COL-I), dentin matrix acid phosphoprotein 1 (DMP1), dentin sialophosphoprotein (DSPP), matrix extracellular phosphoglycoprotein (MEPE), osterix (OSX), osteocalcin (OCN), and osteopontin (OPN) [31]. Some of these genes regulate the expression of runtrelated transcription factor 2 (RUNX2), OSX, and COL-I at the early stage of odontoblast differentiation, while OCN participates in the later stage of differentiation [32]. The control of odontogenic differentiation of dental tissuederived MSCs shows great potential in the application of oral regenerative medicine and cytology treatment.…”
Section: Introductionmentioning
confidence: 99%